From Natural Bio-Resource Waste To Akermanite Bioceramics For Synthetic Bone Substitution - Boey, Zhan Hei (Universiti Sains Malaysia, 2018)
Akermanite is a Si, Ca and Mg contained bio-ceramics that shows bioactive properties in vivo and in vitro conditions. Besides, it also has good controllable mechanical properties and degradation rate. In this study, the formation of akermanite by using natural bio-resource waste is studied. The raw materials include cockle shell, rice husk ash and dolomite. The starting raw materials were heat treated and then weighed according to the molecular formula Ca2MgSiO7. The akermanite was prepared using highenergy planetary ball mill, palletized and sintered at 3 different temperature which were 1150°C, 1200°C and 1250°C for 3 hours with heating rate 5°C per minute. Characterizations of samples were carried out by using XRD, SEM, density measurement, shrinkage measurement. Diametral tensile strength test was also performed on the sintered samples. XRD results showed that only akermanite peaks were identify whereas SEM results showed that the amount of porosity decreases and the grain size increases when sintering temperature increases. The density and shrinkage percentage increases with the increase in sintering temperature. The compressive strength increased when the sintering temperature increases. Among all samples, akermanite samples that was sintered in 1250°C showed remarkable compressive strength.